Implementation of Electronic Medical Records at the Registration Desk of Muhammadiyah Ponorogo General Hospital - Desi Luspitasari; Ani Rosita (Institut Kesehatan Pelamonia, 2025)
Desi Luspitasari, 2025 “Implementation of Electronic Medical Records at the Registration Desk of Muhammadiyah Ponorogo General Hospital“. Scientific Writing. Supervisor: Ani Rosita, S.Kep, Ns, M.Kes. DIII Medical Records and Health Information Study Program, STIKes Buana Husada Ponorogo Electronic Medical Records (EMR) are digital systems that play an important role in improving the efficiency and accuracy of healthcare services, particularly in the patient registration process. This study aims to understand the implementation process of EMR, identify the challenges faced, and evaluate the effectiveness of EMR usage at the registration desk of Rumah Sakit Umum Muhammadiyah Ponorogo. This research uses a qualitative method with a descriptive approach. The data collection techniques used include in-depth interviews with the head of medical records, registration officers, and the information technology team, as well as direct observation and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The research results show that the implementation of RME at Rumah Sakit Umum Muhammadiyah Ponorogo can accelerate the patient registration process from 10–15 minutes to less than 5 minutes, improve data accuracy, and facilitate coordination between units. The challenges faced include network disruptions, data input errors, and staff adaptation to the new system. Improvement efforts are carried out through regular training, periodic evaluations, and enhanced coordination with the information technology team. In conclusion, the implementation of RME at the registration desk of Muhammadiyah General Hospital has proven to support faster, more accurate, and intregated service, in line with the national policy of digital transformation in the health sector. This research recommends improving infrastructure quality, strengthening training for officers, and refining standard operating procedures to support the sustainability of the RME system.